Analisis Pengaruh Penggunaan Air Deck Terhadap Ground Vibration pada Aktivitas Peledakan di Pit Sentuk PT Multi Harapan Utama Provinsi Kalimantan Timur - Dimas Daffa Erlangga; Revia Oktaviani; Lucia Litha Respati; Tommy Trides; Windhu Nugroho (International Forum of Researchers and Lecturers, 2025)
Blasting is an activity that breaks rocks from their parent rock using explosives to create smaller fragments, making the loading and transportation processes easier. One of the environmental impacts of blasting activities is ground vibration. Ground vibration is one of the outcomes of blasting activities, and it is measured using the PPV (Peak Particle Velocity) value. Ground vibration can become a problem for companies if it exceeds the safe vibration quality standard (SNI 7571: 2010), as it can pose a danger to humans and nearby buildings. The Air Deck is an air column in the blast hole that aims to reduce energy vertically, this method can reduce the use of explosives. This research was conducted at the Sentuk Pit of PT. Multi Harapan Utama in East Kalimantan. Observations were made during 42 blast events to determine the impact of the air deck method on the resulting vibration. During the study, the maximum PPV value was 13.87 mm/s, while the minimum PPV value was 1.13 mm/s. The average ground vibration measurement value for non-air deck blasting was 4.40 mm/s, while the average ground vibration measurement value for air deck blasting was 3.95 mm/s. The use of this method also reduced the powder factor value. For non-air deck blasting, the average powder factor value was 0.26 kg/m³, and for air deck blasting, the powder factor value was 0.20 kg/m³, resulting in a 23.08% reduction in explosive usage. To calculate the predicted PPV, scaled distance calculations were used. Based on the predicted PPV calculation results, the deviation from the actual PPV was 1.59 mm/s.